The inability of political pluralism to perform the representative function in established democracies - Mohamed Saber Karim; Rashid Amara Yas (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The political pluralism as a new phenomenal of political life in the democratic state, had been appearance and produced in basic as a result of the nature of the variety and diversity of the society, it’s the propertied and characteristic for the societies in distinction of variety. The search of this phenomenal requires indicated to that big and radically changing and advances which made by the Enlightenment movement and tendency of political Modern, thus the democracy revolutions in each France and United States of America and British is one of those changing and development, which succeed in disintegration of the absolute Monarchies or restricted of them in one side, and in another side the adopting the new foundation of new political system had been accomplished, which excited in the form of democratic representation .The improving of the citizen civil and political right was one of the main goal of this system, whom emerging in groundwork, under the impact of that revolutions and radical movement, requires the participation of the citizen in the administrating of the society. Because of the political plurality nature of the industrial revolution and those democracy revolution in one side, and foundation of democratic representation on the tow basic and essential element ;by the electoral and the legislation authority, on the other side, all those actually called for the accomplishing the electoral of the super leaders and the delegation on the basic of public suffrage which through it citizens outset to elect their delegation, which they the candidate of the political pluralism for those posts . In real that process had been occurred one of the important function of the political pluralism which it the delegation. But this function had faced since early days many big and prominent obstacle and imperfect, especially the main element of political pluralism, mainly what knowing in authority parties, being recession from achieving the really political participation for elect their delegation, this producers have been put the democracy representation suffering big and prominent failing or consumed, which in result making the disability of political pluralist in its citizen representing function , consequently become one of the main phenomenal of political life in this partner of democratic system, especially whom knowing as Intensification democratic system.